A Post-Surgical Stereovision Surprise in an Adult With an Exotropia Since Infancy Previously Managed, at Two Years With Surgery. Issue 1 (16th June 2021) - Littlewood, Revelle A.; Rhodes, Martin; Burke, John
Aim: To describe an unexpected sensory outcome in an adult male who is seeking ocular re-alignment for a psychosocially symptomatic large non-specific exotropia with suppression. The primary diagnosis was infant onset exodeviation of unclear diagnosis, was managed with bilateral strabismus surgery at two years of age, little memory of follow-up. Result: Measurable binocular single vision (BSV) was demonstrable following surgery at 17 years of age, albeit slowly between two weeks and six months postoperatively and subsequently enhanced. His newly acquired sub-optimal BSV led to symptomatic occupation-associated asthenopia. Following two subsequent operations over a 15-year period, he has stable, symptom-free ocular realignment within three prism diopters of orthophoria and performing tasks that require extended periods of near-vision activity. Conclusion: Delayed high levels of stereovision were unexpectedly achieved in an adult with infant onset exotropia with pre-operative sensory suppression that was surgically aligned to near orthophoria. The re-establishment of BSV in such a clinical scenario has to attain a level that is robust enough to meet an individual's social and occupational needs.